Transporter-mediated drug-drug interactions - Study design, data analysis, and implications for in vitro evaluations - Shujun Fu; Feifei Yu; Tao Sun; Zhuohan Hu (Elsevier, 2021)
Drug transporters are well-recognized factors for affecting drug pharmacokinetics, safety and efficacy, which are generally divided into solute carrier (SLC) family and ATP-binding cassette (ABC) family. In contrast to drug-metabolizing enzymes that are largely expressed in the liver and small intestines, transporters are expressed in tissues throughout the whole human body and govern the access of endogenous and exogenous substances to various sites in the body. Therefore, evaluations of transporter-mediated drug-drug interaction (TMDDI), including inhibition and substrate assays, are essentials for ensuring success of pharmaceutical innovation. We reviewed the related Guidance for Pharmaceutical Industries by the regulatory agencies as USFDA, Chinese NMPA, PMDA and EMA analyzed the challenges and summarized the solutions based on the practice by pharmaceutical industries.